Analysis of Generic Porter’s Strategy in Increasing the Competitive Advantage - Iswanti, Putri; Ramadhani, Sri; Atika, Atika (Universitas Pendidikan Indonesia, 2024)
The development of fashion trends has undergone major changes towards modern fashion styles. Many new trends are emerging, one of which is the popularity of Western-style clothing among young people. This phenomenon causes a reduction in people's loyalty to local cultural products, so that many local products are left behind compared to other products. This encourages entrepreneurs operating in the cultural products industry to compete to create excellence in their products so they can compete in the modern era. The method used in this research is a qualitative research method. This research aims to analyze the competitive environment and what strategies are suitable for Kyan Ulos. The results of the research findings are that Kyan Ulos has a fairly high competitive environment, and the strategy that Kyan Ulos can use is the Differentiation Strategy.